(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
Geomorphological studies conducted on the territory of Vayk using special methods created in the GIS made it possible to identify numerous cryptostructures: linearfaults and ring structures (their fragments). This made it possible to understand the features of the localization of mineralization and to assess the prospects of the area for the detection of new significant ore objects.